Effectiveness of biobehavioral therapeutic education in chronic low back pain intensity and disability: a systematic review - Ruíz-del Río, David; La Touche, Roy; Giolito, Gwendoline; Di Bonaventura, Silvia; Grande-Alonso, Mónica; Reina Varona, Álvaro (Journal of MOVE and Therapeutic Science, 2024)
Background: Chronic low back pain (CLBP) is a prevalent musculoskeletal issue that could lead to significant disability. CLBP involves persistent pain and psychological factors contributing to its complexity. Therapeutic education combining cognitive-behavioral approaches may aid in managing CLBP. Objectives: This systematic review evaluates the efficacy of therapeutic education based on a biobehavioral approach in modifying beliefs and promoting active coping strategies in CLBP patients. Methods: Following PRISMA guidelines, we searched PubMed, EBSCO host, and Google Scholar for randomized controlled trials (RCTs) and quasi-experimental studies from March 27 to April 16, 2022, with an update on June 15, 2024. Inclusion criteria focused on adults with CLBP undergoing therapeutic education aimed at behavioral modification. Methodological quality was assessed using the PEDro scale, and risk of bias was evaluated using RoB 2.0. Results: Out of 532 studies, four met the inclusion criteria. The interventions combined therapeutic education with therapeutic exercise or conventional physical therapy. Pain intensity and disability were the main outcomes measured. One study found significant improvements in pain and disability, while others showed trends towards improvement without statistical significance. The quality of evidence was very low. Conclusion: Combining therapeutic education with active coping strategies and other therapies may reduce pain intensity and disability in CLBP patients. However, the evidence quality is very low, highlighting the need for further research.